Preparation of alumina ultrafine powders through acrylamide, starch and glutaric dialdehyde mediated sol–gel method. Issue 6 (1st May 2016) - Zhang, Xiang; Li, Pingyun; Guo, Yizhe; Yang, Xiaomin; Yan, Ting; Guo, Xiaode; Li, Fengsheng
Abstract: Ultrafine alumina powders were synthesized through acrylamide (AM), starch and glutaric dialdehyde mediated aqueous sol–gel process, respectively. Sol and gel formed gradually during drying of the solution due to polymerization reaction between functional groups. The used AM, starch and glutaric dialdehyde could be applied to form perfect matrix for the entrapment of metal ions, giving rise to ultrafine crystalline alumina particles during heating treatment. Al2 O3 nanoparticles with γ crystalline phase were obtained via heating treatment of the dried precursor in air. Then the γ phase transforms to α phase and pure α-Al2 O3 powders could be obtained when the heating temperature was 1473 K. Our results provide a new way of aqueous sol–gel process.